A survey of the christology of Theodore of Tarsus in the Laterculus Malalianus - Siemens, James (Scottish journal of theology, 2007)
Bede's Historia ecclesiastica makes it clear that Theodore of Tarsus, the seventh-century archbishop of Canterbury, is a figure who should command an immense amount of interest. His learning and cosmopolitan formation call upon the scholar to ask what it is that he contributed to the English church in his time and beyond. Yet interest in Theodore as a theologian has been lacking to date, most likely due to the limited amount of material attributable to him. Jane Stevenson's work on the anonymous Laterculus Malalianus in the early 1990s suggested Theodore as the most likely author. That this suggestion has proven consistent with other, cumulative evidence of Theodore's life and work makes the Laterculus an invaluable text for the student investigating his theology. This article seeks to present the theological themes of the text, especially as they relate to the person and work of Christ, and to introduce the reader to Theodore of Tarsus as a figure of interest in the study of early medieval christology.